Application of genetic algorithm for optimal voltage control of the power system / Mohd Supian Yahya - Yahya, Mohd Supian (1998)
This project uses genetic algorithm (GA) for optimal voltage control of the power system and automatically will minimum a system loss. Newton-raphson method is used for load flow calculation and determining the power losses. Although several method of voltage control equipment can be used, the study focussed on compensating capacitors as the variable parameter. The proposed method was applied to 4-busbar, 5-busbar and IEEE 14-busbar system to show its feasibility and capability. All simulation was done on the MATLAB software package version 4.2c. 1.